Analisis Collaborative Governance dalam Rangka Optimalisasi Penerimaaan Pajak Daerah (Studi pada Kota Probolinggo) - Rizky Nugrahani, Shinta Awalia; Putra , Fadillah; Rochmah , Siti (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2024)
Local tax is one of the important sources of local revenue and has great potential and is intended to finance the implementation of local government, including to strengthen broad, real and responsible regional autonomy. The role of taxes in development is seen in all aspects of development carried out by the government. Therefore, the presence of taxes is very important and affects development in a region. Local financial revenues currently obtained are still not optimal, one of which is characterized by a large amount of tax receivables. This study is very important due to the lack of discussion about local taxes in a particular study. In this study, researchers link the tax revenue sector to the Collaborative Governance perspective. This study uses a research method with a Quantitative approach Stuctural Equation Modeling (SEM) method. The results showed that Collaborative Governance has a strong influence on local tax revenue. So that a study is needed that discusses in detail about local tax revenue by looking at the Collaborative Governance perspective. .